Nano-Delivery Revolution: Harnessing Mesenchymal Stem Cell-Derived Exosomes’ Potential for Wound Healing - Pawan Kumar Raghav; Zoya Mann (Biomedicines)
Stem cell transplantation has proven effective in treating acute and chronic wounds, but its limitations, such as low cellular viability and the need for specialized transportation, highlight the necessity for alternative approaches. This review explores the potential of engineered exosomes, containing identified miRNAs/peptides, as a more stable and efficient cell-free therapy for regenerative medicine, particularly in wound healing. The discussion emphasizes the benefits of exosomes, including their stability, reduced damage, and consistent biological activity, paving the way for innovative applications like lyophilized exosomes, mist spray delivery, and exosome-based scaffolds. The exploration of cell-free therapy in this review holds promising implications for advancing wound-healing strategies.